Mechanistic insights into the dual activities of the single active site of l-lysine oxidase/monooxygenase from Pseudomonas sp. AIU 813 - Duangthip Trisrivirat (2020)
© 2020 Trisrivirat et al. l-Lysine oxidase/monooxygenase (l-LOX/MOG) from Pseudomonas sp. AIU 813 catalyzes the mixed bioconversion of l-amino acids, particularly l-lysine, yielding an amide and carbon dioxide by an oxidative decarboxylation (i.e. apparent monooxygenation), as well as oxidative deamination (hydrolysis of oxidized product), resulting in α-keto acid, hydrogen peroxide (H2O2), and ammonia. Here, using high-resolution MS and monitoring transient reaction kinetics with stopped-flow spectrophotometry, we identified the products from the reactions of l-lysine and l-ornithine, indicating that besides decarboxylating imino acids (i.e. 5-aminopentanamide from l-lysine), l-LOX/MOG also decarboxylates keto acids (5-aminopentanoic acid from l-lysine and 4-aminobutanoic acid from l-ornithine). The reaction of reduced enzyme and oxygen generated an imino acid and H2O2, with no detectable C4a-hydroperoxyflavin. Single-turnover reactions in which l-LOX/MOG was first reduced by l-lysine to form imino acid before mixing with various compounds revealed that under anaerobic conditions, only hydrolysis products are present. Similar results were obtained upon H2O2 addition after enzyme denaturation. H2O2 addition to active l-LOX/MOG resulted in formation of more 5-aminopentanoic acid, but not 5-aminopentamide, suggesting that H2O2 generated from l-LOX/MOG in situ can result in decarboxylation of the imino acid, yielding an amide product, and extra H2O2 resulted in decarboxylation only of keto acids. Molecular dynamics simulations and detection of charge transfer species suggested that interactions between the substrate and its binding site on l-LOX/MOG are important for imino acid decarboxylation. Structural analysis indicated that the flavoenzyme oxidases catalyzing decarboxylation of an imino acid all share a common plug loop configuration that may facilitate this decarboxylation.